Circular economy strategy for repurposing coal seam overburden as construction sand in the mining industry - Morton, A; Johnston, S; Taniane, L (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
This paper presents a circular economy strategy for the repurposing of coal seam overburden (CSOB) material as construction sand in the mining industry. The study focuses on the technical and economic feasibility of extracting sand from CSOB and its potential as a sustainable alternative to natural sands in various construction applications. The paper highlights the current challenges in the mining industry regarding the management of mine overburden, which is traditionally considered a waste product. It emphasises the need for a circular economy approach to eliminate waste and re-use materials, with a specific focus on CSOB as a valuable resource. The technical performance of CSOB sand is evaluated through existing examples from India, where CSOB sand has been successfully used as a partial substitute for natural sands in concrete production. The study demonstrates that CSOB sand can meet the specifications set in AS 2758.1-2014 for fine aggregate in Australia. Also discussed is the environmental impact of CSOB sand extraction when used in combination with manufactured sand and natural sands in residual form to reduce the ecological destruction caused by overdredging of marine sands. By utilising CSOB sand, the mining industry can contribute to the sustainable sourcing of construction materials and reduce the ecological footprint associated with sand extraction. Market proximity is examined to assess the feasibility of transporting CSOB sand from remote mining sites to consumer locations. Existing mining infrastructure, such as rail lines, can facilitate transportation and provide a cost-effective and environmentally efficient mode of delivery. Regulatory barriers are identified as a major obstacle to circularisation of the mining industry. The paper calls for changes in current regulations to allow for the processing of non-mineral residual assets, such as CSOBsand, within Australian mining leases. The potential financial benefits of re-using CSOB as sand are discussed, including the reduction of liability in handling mine overburden and the potential for sustainable regional enterprises. Commercial viability, markets and the need for regulatory changes to enable this circular economy initiative within the mining industry require further work.
Keywords: circular economy; sand extraction; coal mine overburden